D-Amphetamine Rapidly Reverses Dexmedetomidine-Induced Unconsciousness in Rats - Kato, Risako; Zhang, Edlyn R.; Mallari, Olivia G.; Moody, Olivia A.; Vincent, Kathleen F.; Melonakos, Eric D.; Siegmann, Morgan J.; Nehs, Christa J.; Houle, Timothy T.; Akeju, Oluwaseun; Solt, Ken (Frontiers in Pharmacology, 2021)
D-amphetamine induces emergence from sevoflurane and propofol anesthesia in rats. Dexmedetomidine is an α2-adrenoreceptor agonist that is commonly used for procedural sedation, whereas ketamine is an anesthetic that acts primarily by inhibiting NMDA-type glutamate receptors. These drugs have different molecular mechanisms of action from propofol and volatile anesthetics that enhance inhibitory neurotransmission mediated by GABAA receptors. In this study, we tested the hypothesis that d-amphetamine accelerates recovery of consciousness after dexmedetomidine and ketamine. Sixteen rats (8 males, 8 females) were used in a randomized, blinded, crossover experimental design and all drugs were administered intravenously. Furthermore, 6 rats with pre-implanted electrodes in the prefrontal cortex (PFC) were used to analyze changes in neurophysiology. After dexmedetomidine, d-amphetamine dramatically decreased mean time to emergence compared to saline (saline:112.8±37.2min; d-amphetamine:1.8±0.6min, P<0.0001). This arousal effect was abolished by pre-administration of the D1/D5 dopamine receptor antagonist, SCH-23390. After ketamine, d-amphetamine did not significantly accelerate time to emergence compared to saline (saline:19.7±18.0min; d-amphetamine:20.3±16.5min, P=1.00). PFC local field potential recordings revealed that d-amphetamine broadly decreased spectral power at frequencies <25 Hz and restored an awake-like pattern after dexmedetomidine. However, d-amphetamine did not produce significant spectral changes after ketamine. The duration of unconsciousness was significantly longer in females for both dexmedetomidine and ketamine. In conclusion, d-amphetamine rapidly restores consciousness following dexmedetomidine, but not ketamine. Dexmedetomidine reversal by d-amphetamine is inhibited by SCH-23390, suggesting that the arousal effect is mediated by D1 and/or D5 receptors. These findings suggest that d-amphetamine may be clinically useful as a reversal agent for dexmedetomidine.